2012
DOI: 10.5772/51481
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Control Performances of an Experimental Web Handling System

Abstract: Robust and good tracking control of the speed and the tension in web handling systems in spite of changes of set point is surely one of the important challenges in the web transport systems future development. In this paper, the authors experimentally demonstrate the real applicability of a decentralized robust control to a multi-span web transport system, which is composed of twelve guide rollers, four main sections mutually interconnected with each other. The overlapping methodology has been applied for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The control results are very good in all the cases by using the automatic tuning: in order to appreciate the slight differences of the different cases, where the setpoint is practically superimposed over the controlled variables values, a zoom of the results in the interesting areas has also been inserted in all the Figures 7-13. presented in this paper with the proposed strategy improve considerably the control performances achieved in [3,7].…”
Section: Figure 4 Setpoint Assumptions For the Proposed Strategymentioning
confidence: 83%
See 1 more Smart Citation
“…The control results are very good in all the cases by using the automatic tuning: in order to appreciate the slight differences of the different cases, where the setpoint is practically superimposed over the controlled variables values, a zoom of the results in the interesting areas has also been inserted in all the Figures 7-13. presented in this paper with the proposed strategy improve considerably the control performances achieved in [3,7].…”
Section: Figure 4 Setpoint Assumptions For the Proposed Strategymentioning
confidence: 83%
“…A solution to the difficulty of the decomposition was introduced since 1998 [2] with a methodology based on a decomposition of the system into subsystems overlapped. The simulation results [2] and some recent experimental tests [3][4] demonstrated that the controller design became easy and that the control performances were better than the conventional decentralized controllers based on a disjoint decomposition and also a PI controller may be adequately used for each subsystem. An important preliminary phase using PI contollers is the opportune tuning of the controller parameters; this operation should be carried out each time that a different reference profile of tension and velocities is requested to the transport platform.…”
Section: Introductionmentioning
confidence: 99%
“…Today many industrial processes employ webs, stored in the form of reels and moved by rollers, to mass produce a wide variety of products made from materials that are characterized by a continuous strip. The possibility of modelling and controlling web handling systems has been studied for a long time (i.e., [1][2][3][4][5][6][7][8]) to limit possible web damage during the transport system's continuous operation. Accurate modelling may be useful for designing the control system or estimating some parameters by comparing them with the experimental tests.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional linear control systems cannot adequately address this problem, even using robust methods. To solve the problem, decentralised control strategies were formulated which break the system down into subsystems and consider only the interactions between the nearest subsystems ( [2,5,7]). Through these particular strategies, a MIMO (multiple-input, multiple-output) system can be traced back to a set of SISO subsystems (single-input single-output) controlled separately with PI controllers turned to use other algorithms to evaluate mutual interactions.…”
Section: Introductionmentioning
confidence: 99%